Assessment of difference in physical activities in urban and rural adolescents of Mangalore - Kundapur, Rashmi; Baisil, Sharon (Indian Journal of Community Health, 2017)
Background: The increasing prevalence of adolescents who are overweight is one of the most pressing public health problems in India. Aims & Objectives: To find the difference in Physical Activities(PA) among urban adolescents to that of rural in Mangalore. Materials and Methods: Cross sectional study among high school students using a standard questionnaire (PAQ-A) to elicit total hours of PA during the past seven days. Results: Average age of the adolescents was 13.9. We could find 56% boys and 44% girls studying in urban schools and 53.3% boys and 46.6 % girls in rural. Seventy seven percent of the total students do running/jogging as their major PA and 66.6% students do cycling. Only 32.8% students had PA while coming to school every day and it was most common among boys in rural schools (55%). Total PA Score for rural areas was 453.5 with a mean of 3.06(out of 5). For Urban areas, total score was 376.3 with a mean of 2.5 and the difference in proportion was statistically significant. Conclusion: We found that the adolescents studying in the schools of rural areas had better physical activities compared to their urban school counterparts.